2022
DOI: 10.1186/s12872-022-02909-x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of circNFIB in myocardial fibrosis alleviation by endogenous sulfur dioxide

Abstract: Background To investigate the role of circNFIB in the alleviation of myocardial fibrosis by endogenous sulfur dioxide (SO2). Methods We stimulated cultured neonatal rat cardiac fibroblasts with transforming growth factor-β1 (TGF-β1) and developed an in vitro myocardial fibrosis model. Lentivirus vectors containing aspartate aminotransferase 1 (AAT1) cDNA were used to overexpress AAT1, and siRNA was used to silence circNFIB. The SO2, collagen, circN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, circNFIB overexpression inhibited CF proliferation based on TGF-β stimulation, whilst inhibition of circNFIB promoted proliferation ( 232 ). circNFIB was found to mitigate myocardial fibrosis induced by SO 2 through suppression of the Wnt/β-catenin and p38 MAPK signaling pathways ( 233 ). circNFIB overexpression could lay a new foundation for a novel option in treating HFpEF.…”
Section: Non-coding Rnas In Pathophysiological Processes Leading To H...mentioning
confidence: 99%
“…Furthermore, circNFIB overexpression inhibited CF proliferation based on TGF-β stimulation, whilst inhibition of circNFIB promoted proliferation ( 232 ). circNFIB was found to mitigate myocardial fibrosis induced by SO 2 through suppression of the Wnt/β-catenin and p38 MAPK signaling pathways ( 233 ). circNFIB overexpression could lay a new foundation for a novel option in treating HFpEF.…”
Section: Non-coding Rnas In Pathophysiological Processes Leading To H...mentioning
confidence: 99%
“…A specific study has outlined the effectiveness of SO 2 in mitigating myocardial fibrosis in diabetic murine models, suggesting that the underlying mechanism involves the attenuation of apoptosis and endoplasmic reticulum stress (ERS) through the suppression of the Hippo-MST signaling pathway [109] (Figure 5). Additionally, it has been demonstrated that endogenous SO 2 enhances the expression of cir-cNFIB, a circular RNA, which in turn inhibits the Wnt/β-catenin and p38 MAPK signaling cascades, thus alleviating the progression of myocardial fibrosis [138] (Figure 5). Another study revealed that endogenous SO 2 might inhibit the ERK signaling pathway to slow myocardial fibroblast proliferation and migration [139].…”
Section: So 2 In the Process Of Myocardial Fibrosis And Other Cardiov...mentioning
confidence: 99%